209k views
25 votes
Which is not equivalent to -4(-3+5)?

Which is equivalent to-(2•-5y)?




Simply and solve using the distributive property.show each step.6(-5-4)

Show your work in all

1 Answer

6 votes

Answer:

-4(-3 + 5) = -4(2) = -8

-(2 · -5y) = -(-10y) = 10y

6(-5 - 4) = 6(-9) = -54

Explanation:

Calculate within parentheses, then apply rule

-(-a) = a or -a(b) = -ab or a(-b) = -ab

-4(-3 + 5) = -4(2) = -8

-(2 · -5y) = -(-10y) = 10y

6(-5 - 4) = 6(-9) = -54

User Dave Richardson
by
5.6k points